Analysing the multiple dimensions of predictive policing's techno-social harms. (17th December 2022) - Wood, Mark A.; Warren, Ian
Abstract : This paper outlines and applies a framework for analysing how technologies can contribute to social harms at individual, institutional, and societal levels. This framework – which we term the technology-harm relations approach – synthesises the insights of postphenomenology and critical realism to detail how harms can emerge from direct human-technology relations (first-order harm relations), as well as the results of the results of human-technology relations (second-order harm relations). To apply this framework, we explore how, through first- and second-order harm relations, predictive policing algorithms might magnify harm through conventional law enforcement activity. We explain how first- and second-order harm relations are by-products of a system that currently generates harm through false ideals of objective, neutral, and non-discretionary enforcement, and that aims to promote consistency while at the same time eroding accountability for decisions utilising automated processes.